2016
DOI: 10.1108/jmp-02-2014-0061
|View full text |Cite
|
Sign up to set email alerts
|

Individual difference predictors of perceived organizational change fairness

Abstract: Purpose – The purpose of this paper is to examine how individual differences influence employees’ attitude toward organizational change. Specifically, the present study examined how and why proactive personality, dispositional resistance to change, and change self-efficacy influence employees’ perceived fairness about the organizational change. Design/methodology/approach – Structural equation modeling was utilized to analyze the survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
2
13
0
1
Order By: Relevance
“…Overall, the present study’s results are in line with the extant research that has shown positive associations among adequate change communication, perceived fairness, and employees’ commitment to change (e.g., Bernerth et al, 2007; Helpap, 2016; Hill et al, 2012; Kernan & Hanges, 2002; Rafferty & Restubog, 2010; Rogiest et al, 2015; Xu et al, 2016). The results relate to recent research that could likewise show a mediating role of procedural fairness in the prediction of employee support for change (Bayraktar, 2019), supporting the importance of procedural fairness for explaining employee reactions to change.…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, the present study’s results are in line with the extant research that has shown positive associations among adequate change communication, perceived fairness, and employees’ commitment to change (e.g., Bernerth et al, 2007; Helpap, 2016; Hill et al, 2012; Kernan & Hanges, 2002; Rafferty & Restubog, 2010; Rogiest et al, 2015; Xu et al, 2016). The results relate to recent research that could likewise show a mediating role of procedural fairness in the prediction of employee support for change (Bayraktar, 2019), supporting the importance of procedural fairness for explaining employee reactions to change.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…On this basis, it is reasonable to assume that employees’ perception of a change’s procedural fairness that comes from top management’s communication serves as an important cue in the individual sensemaking process. This view is in line with findings that have shown links between top management’s change communication and employees’ perceptions of fairness (e.g., Kernan & Hanges, 2002; Xu et al, 2016).…”
Section: Theoretical Background and Development Of Hypothesessupporting
confidence: 91%
See 1 more Smart Citation
“…From the perspective of the benefit received by customers, the satisfactory result (physical) they perceive has a positive and significant effect on the customers' positive emotions (Dzansi 2016;Wang et al 2016;Xu et al 2016). Furthermore, when this result (physical) is capable of influencing and increasing the positive emotions, it will, in turn, impact on future purchase intentions.…”
Section: Resultsmentioning
confidence: 99%
“…Estudos realizados por Xu et al (2016) corroboram com estes resultados à medida que também salientaram que a percepção de autoeficácia positiva e a percepção da existência de justiça estão positivamente associadas a atitudes favoráveis à mudança. Reforçando, assim, os resultados obtidos para o valor organizacional de realização.…”
Section: Tabelaunclassified